2017
DOI: 10.1377/hlthaff.2016.1141
|View full text |Cite
|
Sign up to set email alerts
|

States With Prescription Drug Monitoring Mandates Saw A Reduction In Opioids Prescribed To Medicaid Enrollees

Abstract: Prescription drug monitoring programs are promising tools to use in addressing the prescription opioid epidemic, yet prescribers’ participation in these state-run programs remains low as of 2014. Statutory mandates for prescribers to register with their state’s program, use it, or both are believed to be effective tools to realize the programs’ full potential. Our analysis of aggregate Medicaid drug utilization data indicates that state mandates for prescriber registration or use adopted in 2011–14 were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
103
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 16 publications
4
103
2
Order By: Relevance
“…Consistent with previous research, changes were found to vary dramatically between states and subgroups, and were limited largely to Schedule II opioids [3][4][5][6]. In a country where opioid prescribing nearly quadrupled from 1999 to 2008, it seems likely that much larger and more broad-based declines will be necessary to move the needle significantly on OA-related overdose [7].…”
supporting
confidence: 73%
“…Consistent with previous research, changes were found to vary dramatically between states and subgroups, and were limited largely to Schedule II opioids [3][4][5][6]. In a country where opioid prescribing nearly quadrupled from 1999 to 2008, it seems likely that much larger and more broad-based declines will be necessary to move the needle significantly on OA-related overdose [7].…”
supporting
confidence: 73%
“…One of the largest and most comprehensive studies of prescribing behavior, Buchmueller and Carey (2018), uses Medicare Part D data from 2007-2012 to examine patients' prescription histories. This paper finds that PDMPs have the intended effect on supply, reducing the percentage of enrollees who obtain prescriptions from five or more physicians by more than 8 percent and from five or more pharmacies by more than 15 percent, with no effect on 13 For evidence on Schedule II prescriptions, see Bao et al (2016), Moyo et al (2017), and Wen et al (2017). 7 the mean of the utilization distribution.…”
Section: The Prescription Drug Epidemic and Policy Responsesmentioning
confidence: 88%
“…Universal precautions may include several strategies, including the use of urine toxicology , standardized contracts or agreements , and review of the data accessed from the state PDMP . More information is needed regarding which of these strategies are most beneficial, as well as cost and time effective, in the oncology setting.…”
Section: Risk Assessment and Monitoringmentioning
confidence: 99%